2016
DOI: 10.3390/ma9070552
|View full text |Cite
|
Sign up to set email alerts
|

The First 20 Hours of Geopolymerization: An in Situ WAXS Study of Flyash-Based Geopolymers

Abstract: This study followed the first 20 h of flyash geopolymerization at 70˝C using time resolved Wide Angle X-ray Scattering (WAXS). The extent of dissolution of the amorphous phase of the flyash was determined to range from 29% to 54% for the different formulations trialed. The dissolution rate of the flyash significantly reduced after the first 5 h for all samples. During the formation stage of the geopolymer there were significant temporal variations in the chemistry of the dissolved solution due to the rate of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Hence, in comparison with SEM, this method is well-suited for resolving nanometer-scale surface morphologies and porosity present in rough and irregular fractured samples, including alkali-activated binders. Scattering and diffraction-based techniques have been used to provide insight into AAMs during the initial [109][110][111], medium-term [112], and later-age [113] evolution of gel, crystallite, and pore structure in AAMs. The combination of neutron and X-ray scattering, applied in parallel to provide different aspects of the required information, has also given important new insight into the highlyconnected nature of the pore structure in metakaolin-based AAMs [114].…”
Section: Setting Timementioning
confidence: 99%
“…Hence, in comparison with SEM, this method is well-suited for resolving nanometer-scale surface morphologies and porosity present in rough and irregular fractured samples, including alkali-activated binders. Scattering and diffraction-based techniques have been used to provide insight into AAMs during the initial [109][110][111], medium-term [112], and later-age [113] evolution of gel, crystallite, and pore structure in AAMs. The combination of neutron and X-ray scattering, applied in parallel to provide different aspects of the required information, has also given important new insight into the highlyconnected nature of the pore structure in metakaolin-based AAMs [114].…”
Section: Setting Timementioning
confidence: 99%
“…The maximum intensity cannot be directly related to the nanoscale morphology of the material, therefore, but instead will be a combination of scattering from the material and contributions from the experimental setup. By examining SAS data from the literature for AAMs [43][44][45], however, the intensity at 0.3-0.4 Å -1 can be used to qualitatively analyze the formation of pores or a layered structure in the paste as it evolves. Although previous studies on metakaolin-based IPs have shown that this SAS region is attributed to pores in the paste [43], a layered structure cannot be discounted at this stage of the investigation as calcium-silicate-hydrate-type gels typical of Portland cements and Ca-rich AAMs/IPs can give rise to a basal peak in reciprocal space positioned between ~ 0.35 ≤ Q ≤ 0.8 [46].…”
Section: Evolution In Reciprocal Spacementioning
confidence: 99%
“…At Load 0, in the case of the cubic iron oxide phase, there is a large distribution in the strain values (−2 × 10 −3 to 4 × 10 −3 ), much greater than the per component uncertainty of ~10 −4 which has been previously determined for this technique 58 . This large variation in strain across the cubic iron oxide crystals can be attributed to variation in lattice parameter (calculated to be in the range of 8.344–8.404 Å) due to substitution of Fe atoms by Ca, Al, Mg, Mn or Ti during coal combustion 47,59 and possible local variations of shrinkage stresses. Comparing elastic strains in the loading direction at various load steps, it can be seen that on average the compressive elastic strains in both phases increased as the macroscopic load applied to the specimen was increased (refer to lines plotted across Fig.…”
Section: Resultsmentioning
confidence: 99%